Dry Eye Disorder in Adult Patients Having Hyperthyroidism (Medical Forum Monthly, 2024)
Objective: The aim of this study was to note the frequency of dry eye disorder in adult patients having hyperthyroidism.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Ophthalmology of Bahawal Victoria Hospital, Quaid-e-Azam Medical College, Bahawalpur from March 2016 to September 2016.Materials and Methods: A total of 60 patients, aged 18 to 60 years, with hyperthyroidism were enrolled in this study. Fluorescein strips along with slit lamp and pen torch were used for the evaluation of dry eye disorder. The dry eye was further graded according to the severity level 1, 2, 3 and 4 with help of history, clinical findings and schirmer test.Results: Amongst a total of 60 patients, 22 (36.7%) were male and 38 (63.3%) female. Overall mean age was noted to be 39.53 years with a standard deviation of 6.9 years and most of the patients, 28 (46.7%) were between 36-50 years. Overall out of 60 patients, dry eye disorder was found to be in 50 (83.3%) cases. When patients having dry eye disorder were compared with normal eyes, except duration of hyperthyroidism as more than 10 years (p value = 0.021), no significant difference was found with regards to gender (p value = 0.632), age (p value = 0.459), area of residence (p value = 0.624) or history of smoking (p value = 0.275).Conclusion: Frequency of dry eye disorder in adult patients having hyperthyroidism was noted as high. Duration of hyperthyroidism seemed to promote dry eye disorder.